Some Results on the Growth of Polynomials (Analysis in Theory and Applications, 2017)
In this paper, we have studied the Lacunary type of polynomials and proveda result which generalizes as well as refines some well-known polynomial inequalitiesregarding the growth of polynomials not vanishing inside a circle. Further, the papercorrects the proofs of some already known results.
Keywords: Lacunary polynomial; Growth; Bernstien-inequality.